2021
DOI: 10.3389/fneur.2021.636719
|View full text |Cite
|
Sign up to set email alerts
|

Use of EP3533-Enhanced Magnetic Resonance Imaging as a Measure of Disease Progression in Skeletal Muscle of mdx Mice

Abstract: As putative treatments are developed for Duchenne muscular dystrophy (DMD), sensitive, non-invasive measures are increasingly important to quantify disease progression. Fibrosis is one of the histological hallmarks of muscular dystrophy and has been directly linked to prognosis. EP3533 is a novel contrast agent with an affinity to collagen 1 that has demonstrated a significant and high correlation to ex vivo fibrosis quantification. Halofuginone is an established anti-fibrotic compound shown to reduce collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Subsequently, we then reported that pre-treatment with halofuginone mitigated the atrophy of the gastrocnemius muscle during hindlimb suspension. These positive effects of halofuginone treatment are consistent with reports showing that this dose (i.e., 0.25 μg/g) and frequency of administration (i) were very well-tolerated in mice for up to 3 months and (ii) improved muscle-cell survival, promoted membrane repair, and improved muscle performances in models of muscular dystrophies [31,33,[58][59][60]. However, none of these studies explored whether the potential effect of HF would involve the ATF4 pathway.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Subsequently, we then reported that pre-treatment with halofuginone mitigated the atrophy of the gastrocnemius muscle during hindlimb suspension. These positive effects of halofuginone treatment are consistent with reports showing that this dose (i.e., 0.25 μg/g) and frequency of administration (i) were very well-tolerated in mice for up to 3 months and (ii) improved muscle-cell survival, promoted membrane repair, and improved muscle performances in models of muscular dystrophies [31,33,[58][59][60]. However, none of these studies explored whether the potential effect of HF would involve the ATF4 pathway.…”
Section: Discussionsupporting
confidence: 89%
“…To evaluate the effects of a periodic halofuginone (HF) (#32481, Sigma, Saint-Quentin-Fallavier, France) administration, we performed a first protocol where mice received either HF (0.25 µg/g) or water (H 2 O) by gavage 3 times a week for 1 to 4 weeks (n = 6 animals per group). This dose was reported as well tolerated over longer periods [31,33,60]. Gastrocnemius muscle was sampled 6 h after the last HF/H 2 O administration at the end of each week.…”
Section: Methodsmentioning
confidence: 99%
“…The agent was a cyclic peptide with three gadolinium moieties, and the dense scar tissue of a mouse myocardial infarct was shown to enhance preferentially relative to surrounding healthy myocardium. Since the first demonstration in an infarction model, subsequent studies extended its application to mouse models of liver (17), pulmonary (18), and skeletal muscle (19) fibrosis. All studies confirmed superior sensitivity and specificity of collagentargeted agents for fibrotic tissue compared to non-targeted counterparts.…”
Section: Collagen-targeted Gadolinium-based Contrast Agentsmentioning
confidence: 99%
“…Therefore, an accurate imaging technique for fibrosis analysis is desired. Recently, several studies have also shown that the use of ColI-targeted imaging probe in MR imaging can benefit the fibrosis diagnosis in Duchenne muscular dystrophy ( Murphy et al, 2021 ), nonalcoholic steatohepatitis ( Zhou et al, 2020 ), diffuse cardiac fibrosis ( Ezeani et al, 2021 ) and pancreatic cancer ( Polasek et al, 2017 ). In this study, we generated an CD fibrosis rat model to evaluate the strategy of targeting ColI for staging fibrosis in CD and to compare its efficiency with Gd-DTPA, which is a common MR imaging contrast medium.…”
Section: Introductionmentioning
confidence: 99%